INTENTION TO SEND GIFTS IN LIVE STREAMING COMMERCE: THE ROLE OF EMOTIONAL ATTACHMENT AND ENGAGEMENT (Third Sector Social Economic Review, 2025)
Live streaming commerce tends to develop continuously with the digital generation. Therefore, this study focus on gift-giving behavior in live streamings. The purpose of the study is to explore the emotional and engagement factors that influence the intention to give gifts in live broadcast commerce. Accordingly, data were collected from 492 live steaming viewers. The data obtained were analyzed in SPSS 22 and AMOS 24 package programs. As a result of the analysis, emotional attachment and engagement positively affected the intention of viewers to send gifts. In addition, emotional attachment affected the engagement of the viewers. The antecedent variables of emotional attachment were attractiveness, perceived entertainment, pleasure and arousal while the antecedent variables of engagement were trustworthiness, expertise, professionalism, price discount, social presence and self-esteem. For this reason, companies, influencers or sellers who trade live streaming can increase the intention of users to send gifts by first ensuring emotional attachment and then converting it into engagement.
Keywords: Live Stream Commerce; Emotional Attachment; Engagement; Intention to Send a Gift; AMOS